2019
DOI: 10.5539/elt.v12n2p17
|View full text |Cite
|
Sign up to set email alerts
|

Spokes in the Wheels of CLIL for Multilingualism or How Monolingual Ideologies Limit Teacher Training

Abstract: In line with van Kampen et al.’s (2018) research about specialist and practitioner perceptions on the goals for CLIL in the Netherlands, the present study addresses Hüttner, Dalton-Puffer and Smit’s (2013) call for investigating teachers’ beliefs about CLIL in European countries like Spain where this teaching approach is highly institutionalized. Unlike the aforementioned studies, though, ours focuses on novice subject teachers in Primary education. More specifically, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…Secondly, linguistic skills and progress in those skills are an area of principal concern for students in bilingual teaching programmes (Madrid & Julius, 2020) and in general for the future of EMI programmes (Pérez-Cañado, 2020;Lasagabaster, 2019). The results here showed that students seemed to feel positively about their own skills and progress in English in the program, and hold extraordinary expectations for the degree and for their own future linguistic progress, which echoes previous research on pre-service students' focus on linguistic gains as motivation to study (Martí & Portolés, 2019). In fact, students expected their level of English to increase considerably by the end of the degree, and close to 50% of respondents expected to finish the degree at the highest level of language proficiency, CEFR C2 (Proficient).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Secondly, linguistic skills and progress in those skills are an area of principal concern for students in bilingual teaching programmes (Madrid & Julius, 2020) and in general for the future of EMI programmes (Pérez-Cañado, 2020;Lasagabaster, 2019). The results here showed that students seemed to feel positively about their own skills and progress in English in the program, and hold extraordinary expectations for the degree and for their own future linguistic progress, which echoes previous research on pre-service students' focus on linguistic gains as motivation to study (Martí & Portolés, 2019). In fact, students expected their level of English to increase considerably by the end of the degree, and close to 50% of respondents expected to finish the degree at the highest level of language proficiency, CEFR C2 (Proficient).…”
Section: Discussionsupporting
confidence: 85%
“…Since they are both students and pre-service teachers at the same time, we will use both terms throughout this paper. A key area in need of continuing research for pre-service teachers is that of stakeholder perceptions, an understudied field (Martí & Portolés, 2019). This is particularly important when considering the weight of the future work of these pre-service teachers as bilingual programmes continue to trend upward and higher education looks to accommodate this need.…”
mentioning
confidence: 99%
“…Moving to pre-service teachers, similar findings have been made (Fischer & Lahmann, 2020;Martí & Portolés, 2019;Portolés & Martí, 2020;Schroedler & Fischer, 2020). In the Valencian region, the study conducted by Martí and Portolés (2019) explored 110 prospective teachers' beliefs about Content and Language Integrated Learning (CLIL) in multilingual settings. Participants' opposing views on the use of multiple languages in the CLIL classroom were noted.…”
Section: Predictors Of Teachers' Beliefssupporting
confidence: 58%
“…; Martí, O., & Portolés, L. (2019). Spokes in the wheels of CLIL for multilingualism or how monolingual ideologies limit teacher training.…”
mentioning
confidence: 99%
“…Based on the viewpoints of Nightingale & Safont [10], Portoles & Marti [11], Reisner [12], etc., we come to the conclusion that a polylingual personality is not just an individual with different sets of speech communication capabilities. Furthermore, it is a culture-historical persona possessing national heritage and social value, willing to apply accumulated nation-specific linguistic and cultural knowledge of one's own country and the target-language country in the professional activity, displaying interpersonal skills, empathy, and tolerance as professionally important attributes [11].…”
Section: Introductionmentioning
confidence: 99%